Pre-hospital Assessment of the Role of Adrenaline: Measuring the Effectiveness of Drug administration In Cardiac arrest (PARAMEDIC-2): Trial protocol. (November 2016) - Perkins, Gavin D.; Quinn, Tom; Deakin, Charles D.; Nolan, Jerry P.; Lall, Ranjit; Slowther, Anne-Marie; Cooke, Matthew; Lamb, Sarah E.; Petrou, Stavros; Achana, Felix; Finn, Judith; Jacobs, Ian G.; et al.
Abstract: Despite its use since the 1960s, the safety or effectiveness of adrenaline as a treatment for cardiac arrest has never been comprehensively evaluated in a clinical trial. Although most studies have found that adrenaline increases the chance of return of spontaneous circulation for short periods, many studies found harmful effects on the brain and raise concern that adrenaline may reduce overall survival and/or good neurological outcome. The PARAMEDIC-2 trial seeks to determine if adrenaline is safe and effective in out-of-hospital cardiac arrest. This is a pragmatic, individually randomised, double blind, controlled trial with a parallel economic evaluation. Participants will be eligible if they are in cardiac arrest in the out-of-hospital environment and advanced life support is initiated. Exclusions are cardiac arrest as a result of anaphylaxis or life threatening asthma, and patient known or appearing to be under 16 or pregnant. 8000 participants treated by 5 UK ambulance services will be randomised between December 2014 and August 2017 to adrenaline (intervention) or placebo (control) through opening pre-randomised drug packs. Clinical outcomes are survival to 30 days (primary outcome), hospital discharge, 3, 6 and 12 months, health related quality of life, and neurological and cognitive outcomes (secondary outcomes). Trial registration (ISRCTN73485024).